2012
DOI: 10.1016/j.biortech.2012.06.099
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the redox mediator sodium anthraquinone-2,6-disulphonate (AQDS) on the reductive decolourisation of the azo dye Reactive Red 2 (RR2) in one- and two-stage anaerobic systems

Abstract: This work assessed the impact of the redox mediator sodium anthraquinone-2,6-disulphonate (AQDS) on the reductive decolourisation of the azo dye Reactive Red 2 (RR2) in one- and two-stage anaerobic systems (R(1) and R(2), respectively). The two-stage system achieved better colour removal efficiencies (52-62%) than the single-stage system (23-33%) in the absence of AQDS. Addition of AQDS accelerated the electrons transfer from the substrate (ethanol) to the dye, which increased the colour removal efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The average DE values in R 2 achieved in this study are comparable to those of the continuous reactors with continued addition of free quinones. 5 , 26 By considering the operation cost of free quinones, the nanocomposite showed a great potential on industrial applications. Moreover, the k values were higher than that obtained by the addition of MHA in our previous study, 4 and the enhancement times of DRs were larger than the reactors feeding with free and/or immobilized humic acid.…”
Section: Resultsmentioning
confidence: 99%
“…The average DE values in R 2 achieved in this study are comparable to those of the continuous reactors with continued addition of free quinones. 5 , 26 By considering the operation cost of free quinones, the nanocomposite showed a great potential on industrial applications. Moreover, the k values were higher than that obtained by the addition of MHA in our previous study, 4 and the enhancement times of DRs were larger than the reactors feeding with free and/or immobilized humic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Keskinkan and Lugal Göksu (2007) also stated that the variation in HRT is an important factor in dye treatment and the treatment performance increased with the increasing HRT in their study. Rodrigues da Silva et al (2012) also observed that a short HRT (3 h) was not sufficient to allow a higher decolorization, suggesting that a short HRT was not long enough to allow the dye reduction satisfactory. According to the legal discharge limit for color intensity in Korea (400 ADMI; Oh et al 2004), the developed biological methodology in current study can be potentially used to treat real dyeing wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…All these available technologies have limitations, including the inefficient mineralization of the synthetic dyes, dense solution disposal, high energy consumption, high operation costs, and the excessive production of sludge, etc. [18,19,20]. Therefore, there are intensive demands for highly efficient and progressive newer technologies for the complete removal of the contaminants from the aquatic environment [21,22].…”
Section: Introductionmentioning
confidence: 99%